The amazing Gribbles - "Cowley, Joy" (Hawthorn; Mimosa McGraw-Hill, 2007)
Fred Gribble invents robots, his sister Asia transforms the house, and their little brother Silas makes fireworks (and only a few mistakes). When their cook, Mrs Munch, is frightened away by Creep, the pet python, the Gribbles find a way to make dinner. Robot JB007 with its cooking-tool fingers is just what's needed
Donated by "Book Planet", Dated 18-4-2025.
Keywords: Robots Juvenile fiction